2018
DOI: 10.3329/bjnm.v18i2.35222
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Functional Status in Chronic Kidney Disease

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
(4 reference statements)
3
5
0
Order By: Relevance
“…In our study, majority of patients included in the study with Chronic Kidney Disease were in the age group of 50-60 years (Table 1). Similar to our study, Md Mosharruf Hossain et al [17] showed that prevalence of thyroid dysfunction in patients with Chronic Kidney Disease were more in the age group of 50-60 years. In contrast to our study, Abhishek Gupta et al [4] showed that patients of Chronic Kidney Disease with thyroid dysfunction were more in the age group of 40-50 years.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, majority of patients included in the study with Chronic Kidney Disease were in the age group of 50-60 years (Table 1). Similar to our study, Md Mosharruf Hossain et al [17] showed that prevalence of thyroid dysfunction in patients with Chronic Kidney Disease were more in the age group of 50-60 years. In contrast to our study, Abhishek Gupta et al [4] showed that patients of Chronic Kidney Disease with thyroid dysfunction were more in the age group of 40-50 years.…”
Section: Discussionsupporting
confidence: 91%
“…One of the major worldwide public health problems is CKD. According to WHO, 2004, they are the 12th cause of death and 17th cause of disability in the world [17]. In patients with CKD, several alterations in thyroid function has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports suggest that progression of CKD is associated with having a number of complications, including thyroid dysfunction (4). Impairment in kidney function leads to disturbed thyroid physiology, all levels of the hypothalamic pituitary thyroid axis may be involved, including alterations in hormone production, distribution, and excretion (11). Leptin is linked to the development of CKD in the absence of obesity, as patients with ESRD have an estimated 4-7.5 fold increase in plasma leptin concentration (hyperleptinemia) compared with healthy control subjects (12).…”
Section: Discussionmentioning
confidence: 99%
“…These finding are similar to the results from (15), who showed significant increase in the level of TSH in the CKD patients compared with the controls. In the existing (11,16,17). The result of current study is in conflict with study done by Khatiwada et al, (18), who observed decreasing trend for T3 and T4 levels (though the decrease was not significant), and increasing trend for TSH level (significant rise) across CKD stages 3-5, which suggest that TSH level increases with the progression of renal impairment.…”
Section: Discussionmentioning
confidence: 99%